2016
DOI: 10.18632/oncotarget.10198
|View full text |Cite
|
Sign up to set email alerts
|

SFMBT2 (Scm-like with four mbt domains 2) negatively regulates cell migration and invasion in prostate cancer cells

Abstract: Metastatic prostate cancer is the leading cause of morbidity and mortality in men. In this study, we found that expression level of SFMBT2 is altered during prostate cancer progression and has been associated with the migration and invasion of prostate cancer cells. The expression level of SFMBT2 is high in poorly metastatic prostate cancer cells compared to highly metastatic prostate cancer cells. We also found that SFMBT2 knockdown elevates MMP-2, MMP-3, MMP-9, and MMP-26 expression, leading to increased cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto‐oncogene necessary for self‐renewal and maintenance of murine hematopoietic stem cells . The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129–2) confirmed in our study have also shown hypermethylation in other malignancies (Table ) . Among them, SFMBT2 and MIR129–2 have been shown to act as tumor suppressors.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…HOXB4, as a hematopoietic transcription factor, downregulates the expression of Prdm16, which is a proto‐oncogene necessary for self‐renewal and maintenance of murine hematopoietic stem cells . The other eight frequently methylated candidates (CCDC181, DPP4, BEND4, CTNND2, ELMO1, SFMBT2, C1QL3, MIR129–2) confirmed in our study have also shown hypermethylation in other malignancies (Table ) . Among them, SFMBT2 and MIR129–2 have been shown to act as tumor suppressors.…”
Section: Discussionsupporting
confidence: 78%
“…Among them, SFMBT2 and MIR129–2 have been shown to act as tumor suppressors. SFMBT2 negatively regulates migration and invasion by targeting MMP‐9 and MMP‐26 . MIR129–2 suppresses migration and invasion by directly inhibiting HMGB1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al ( 33 ) demonstrated that transcriptional repression was associated with human SFMBT2, which binds preferentially to methylated histone H3 and H4. In addition, it has been revealed that SFMBT2 regulates cell proliferation via epigenetic regulation of homeobox B13 gene expression in the DU145 prostate cancer cell line ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin-enriched extracts were prepared as described before (Gwak et al, 2016). Briefly, U2OS cells were transfected with WT MBTD1-3xFlag, MBTD1-A236D/L259D/L263D-3xFlag mutant or an empty vector (4µg) using Lipofectamine 2000.…”
Section: Chromatin Extractsmentioning
confidence: 99%